Association Between Cognitive Function and Early Life Experiences in Patients with Alcohol Use Disorder - Cheng, Fangshuo; Cui, Shu; Zhang, Chao; Zhang, Ling; Wang, Lei; Yuan, Qiuyu; Huang, Cui; Zhang, Kai; Zhou, Xiaoqin (Frontiers in Psychiatry, 2020)
Abstract Introduction: Early life experiences could be potential risk factors for in the development of alcohol use disorder. In similar circumstances, it might also influence cognitive impairment later in life. However, the association between experiences in early life and cognitive function during alcohol use disorder is unclear. The current study examines the effects of early social environment and experiences on cognitive function in patients with alcohol use disorder. Methods: A total of 37 adult male alcohol use disorder patients and 30 healthy control subjects were enrolled in the study. The cognitive function of the participants was assessed with the MATRICS cognitive consensus battery. The Childhood Trauma Questionnaire and Revised Adult Attachment Scale were used to evaluate the early life experiences. Results: Compared with the HC group, alcohol use disorder group reported higher levels of childhood abuse and were more likely to form insecure attachment style. alcohol use disorder patients who experienced trauma performed worse in terms of discrete cognitive parameters such as social cognition, reasoning and problem solving compared with patients without trauma. Importantly, emotional neglect and social comfort were significantly associated with individual social cognitive skills. Conclusions: Our results suggest that the cognitive function of patients with alcohol use disorder, especially social cognitive function, is affected by early life experiences.